ANALISIS NOVEL AIR MATA TERAKHIR BUNDA KARYA KIRANA KEJORA DENGAN PEDEKATAN STRUKTURALISME GENETIK - Maya Permata Sari; F.A. Milawasri; Nurulanningsih . (Jurnal Didascein Bahasa, 2017)
This study aims to describe intrinsicic elements, social culture life from particular community and world view author in novel Air Mata Terakhir Bunda by Kirana Kejora. The method is descriptic analysis. It is used to describe facts and then analyze data. The source of data is best seller novel entitled Air Mata Terakhir Bunda karya Kirana Kejora, seventh printed at 2013 and was filmed in 2013, it is adaptable from fact stories, 202 pages and published by HI-fest Publishing Jakarta Timur. Based on results and discussion, it could be concluded that Air Mata Terakhir Bunda consists of supported factor that is intrinsic element and additional factor which is figure and strong character, mixed plot, background in Sidoarjo and Jakarta year 2006-2011, point of view, figure of speech Indonesian mix Javanese. Then, it is also derived from social culture author from facebook community which has several famous writer and art workers. The social life improvement from the author become better, and also it happened in story Air Mata Terakhir Bunda. The writer point of view is social humanism which has humanism social and transedental humanism. It was inspired from Lumpur Lapindo tragedy in Sidorjo. The values which could be found in Air Mata terakhir Bunda were education,social and religous values.Keywords : structuralism, genetic analysis and humanism.